LINC01235 Promotes Clonal Evolution through DNA Replication Licensing‐Induced Chromosomal Instability in Breast Cancer - Qi Zhang; Xuliren Wang; Zhibo Shao; Yi Zhang; Liyi Zhang; Ming Chen; Xujie Zhou; Han Zhu; Yue Zhou; Xinya Lu; Pei Li; Weiru Chi; et al. (Advanced Science)
Abstract Despite the development of HER2‐targeting drugs such as trastuzumab and T‐DXd, treatment resistance is a substantial challenge, often leading to relapse and distant metastasis. Tumor heterogeneity in HER2‐positive breast cancer drives the evolution of resistant clones following therapeutic stress. However, the targetable drivers of anti‐HER2 treatment resistance are not thoroughly identified. This study aims to use neoadjuvant‐targeted therapy cohorts and a patient‐derived organoid in vitro treatment model to uncover the potential targetable drivers of anti‐HER2 treatment resistance. it is found that LINC01235 significantly enhances DNA replication licensing and chromosomal instability, fostering clonal expansion and evolution, and ultimately increasing resistance to therapeutic interventions. LINC01235 regulates global H3K27ac, H3K9ac, and H3K36me3 modifications, promotes H2A.Z expression in regulatory regions, and increases the accessibility of DNA licensing factors to their promoter regions. XRCC5 is identified as a key component for maintaining genomic stability, crucial for LINC01235's role in replication licensing. Furthermore, therapeutic strategies targeting LINC01235, including the use of antisense oligonucleotides or ATR inhibitors, which showed promise in overcoming treatment resistance are explored. These findings underscore the pivotal role of LINC01235 in driving resistance mechanisms and highlight novel avenues for targeted therapies to improve the outcomes of patients with HER2‐positive breast cancer.